The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/17435390.2018.1476986
|View full text |Cite
|
Sign up to set email alerts
|

Modeling gold nanoparticle biodistribution after arterial infusion into perfused tissue: effects of surface coating, size and protein corona

Abstract: A detailed understanding of the factors governing nanomaterial biodistribution is needed to rationally design safe nanomedicines. This research details the pharmacokinetics of gold nanoparticle (AuNP) biodistribution after arterial infusion of 40 or 80 nm AuNP (1 μg/ml) into the isolated perfused porcine skin flap (IPPSF). AuNP had surface coatings consisting of neutral polyethylene glycol (PEG), anionic lipoic acid (LA), or cationic branched polyethylenimine (BPEI). Effect of a porcine plasma corona (PPC) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…As a result, smaller GNPs can contribute to an inflammatory response, due to their interactions with these proteins, highlighting the necessity for proper functionalization [91]. Another factor that impacts biodistribution is the surface charge, which can be controlled by various surface conjugations, such as with PEG [92,93]. The addition of PEG to 20 nm glucose-functionalized GNPs has been shown to increase the half-life period from 1.23 h to 6.17 h [94].…”
Section: Intracellular Fate Of Gold Nanoparticles Based On Their Physmentioning
confidence: 99%
“…As a result, smaller GNPs can contribute to an inflammatory response, due to their interactions with these proteins, highlighting the necessity for proper functionalization [91]. Another factor that impacts biodistribution is the surface charge, which can be controlled by various surface conjugations, such as with PEG [92,93]. The addition of PEG to 20 nm glucose-functionalized GNPs has been shown to increase the half-life period from 1.23 h to 6.17 h [94].…”
Section: Intracellular Fate Of Gold Nanoparticles Based On Their Physmentioning
confidence: 99%
“…Biomolecule coronas may transform NMs by also modulating their colloidal stability and/or zeta potential. 4,10,11,22,29,35,[38][39][40]44,45,47,48,54,55,65 Summarizing the results of numerous studies, (patho)biological and ecological environments seem to be facing mainly negatively-charged, protein corona-covered NMs, irrespective of the NM's initial zeta potential. 46,55,59,[66][67][68] Although we only tested a selection of relevant NMs, our data demonstrates that binding to also negatively charged bacteria occurs and thus, that binding cannot be predicted by colloidal electrostatics alone in the absence or presence of biomolecules.…”
Section: Resultsmentioning
confidence: 99%
“…From those papers, morphological comparison studies of nanomaterials showed that the dissolution behavior and the biological effects of wire-shaped nanomaterials are distinctly different from the dissolution behavior and adverse effects of nanosphere or nanoplate analogues (M€ uller et al 2010;George et al 2012;Sohn et al 2015;Nam and An 2019). Intrinsic properties such as size, surface chemistry, and charge of nanowires could play a key role in controlling their adverse effects to organisms, as has been widely confirmed by studies on spherical nanomaterials (Nam and An 2019;Majumdar et al 2019;Riviere et al 2018). To the best of our knowledge, less than 15 studies have been published in which the impact of physicochemical properties of nanowires on their toxic effects were examined.…”
Section: Introductionmentioning
confidence: 91%